How Susceptible are Skills to Obsolescence? A Task-Based Perspective of Human Capital Depreciation - Sonja Walter; Jeong-Dong Lee (Foresight and STI Governance)
This article investigates the link between human capital depreciation and job tasks, with an emphasis on potential differences between education levels. Using data from the German Socio-Economic Panel, fixed effects panel regression is applied to estimate an extended Mincer equation based on Neumann and Weiss’s model. Human capital gained from higher education levels depreciates at a faster rate than other human capital. The depreciation rate is also higher for specific skills compared to general skills. Moreover, the productivity-enhancing value of education diminishes faster in jobs with a high share of non-routine interactive, non-routine manual, and routine cognitive tasks. These jobs are characterized by greater technology complementarity or more frequent changes in core-skill or technology-skill requirements.  The presented results point to the urgency of elaborating combined labor market and educational and lifelong learning policies to counteract the depreciation of skills. Education should focus on equipping workers with more general skills in all education levels and adapt educational programs to take into account the rapid upgrade of production technologies and changing competency requirements.